STRUKTUR KOMUNITAS PLANKTON DI PERAIRAN TELUK PALU DAN PEMANFAATANNYA SEBAGAI SUMBER BELAJAR - Sabran, Moh (JSTT, 2016)
This research aimed to: 1) describe the structure of plankton community in the Gulf of Palu; 2) explain the relation between the physical-chemical waters conditions and the plankton community in the Gulf of Palu; 3) producea biological learning media in form of book as a learning resource. This research has been employed a quantitative descriptive method by using field survey and laboratory. The research samples have been collected three times through a sampling technique by using the plankton net. The researchâ€™s results have found 49 types of plankton which consist of 27 types of phytoplankton and 22 types of zooplankton from various taxonomic categories. The plankton abundance is around 2.818 to 4.072 cell per liter. The value of planktonâ€™s biodiversity index is 2.81 to 3.15 which shows that the community establishment is good (stable) and the uniformity index located at 0.98 to 0.99. Based on achieved value, which is in range of 0,040 to 0,065, the dominance value index has also shown that there is no dominant type. From the Morisitaâ€™s index calculation that intended to determine the distribution a pattern of plankton types, this research has found that around of 78 percent of phytoplankton is uniform and 22 percent is regular in their distribution patterns. Meanwhile, for the zooplankton the distribution pattern is 86 in form of uniform distribution and 14 percent in a group formation. The result of assessment produced by this Knowing Planktonâ€™s monograph, both its content and design, has finally declared â€œfeasibleâ€ with the percentage of 95.55 percent.Â